UNIT 8.10 Immunoblotting and Immunodetection. (1st August 2016) - Ni, Duojiao; Xu, Peng; Gallagher, Sean
Abstract : Immunoblotting (western blotting) is used to identify specific antigens recognized by polyclonal or monoclonal antibodies. This unit provides protocols for all steps, starting with solubilization of the protein samples, usually by means of SDS and reducing agents. Following solubilization, the material is separated by SDS‐PAGE and the antigens are electrophoretically transferred to a membrane, a process that can be monitored by reversible staining with Ponceau S. The transferred proteins are bound to the surface of the membrane, providing access to immunodetection reagents. After nonspecific binding sites are blocked, the membrane is probed with the primary antibody and washed. The antibody‐antigen complexes are tagged with fluorophores, horseradish peroxidase, or alkaline phosphatase coupled to a secondary anti‐IgG antibody, and detected using appropriate fluorescent imaging technologies or with chromogenic or luminescent substrates. Finally, membranes may be stripped and reprobed. © 2016 by John Wiley & Sons, Inc.